Summerland - French, Jackie (Australia HarperCollins Publishers, 1997)
Iddy cannot remember her name, or where she comes from. But she finds understanding and friends in the peace of Summerland. One day the shadowmen arrive ... and Iddy is the only one who can save the village ... if only she can get past the fear.